Strategi Pembelajaran Pelafalan Bahasa Inggris Materi Front Office Melalui Kartu Tematik Bagi Mahasiswa Manajemen Perhotelan Universitas Dhyana Pura - Made Suardika Jaya (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2017)
The ability to pronounce specific terms about the concept of front office is a crucial aspect which should be mastered by the students who learn about the field of hotel management. The learning process in the classroom still becomes the main key to reach the excellent achievement in speaking section. The main purpose of this research is to increase the pronunciation ability of the students, specifically for terms of front office concept, through the utilization of media for assisting the language learning process. The use of thematic cards method could be a proper choice to be applied in optimising the learning process which will increase the students’ comprehension towards the lessons delivered by the lecturer. This method is scientifically proven for enhancing the students’ pronunciation ability in this research, reaching the point of 68.97%. Besides pronunciation aspect, there are four other assessment aspects which have risen notably; the aspect of intonation aspect (reached the point of 67.59%), fluency (63.45%), expression (67.59%), and structure (68.28%). The result of this research proves that the classical learning process which is supported by the application of thematic cards could raise the ability of the students to pronounce the terms significantly via the implementation of the test in two cycles.